THE REPRESENTATION OF SUNDANESE FOLKLORE NYI MAS SANGHYANG DEWI SRI IN THREE LANGUAGES - Erlina Zulkifli Mahmud; Taufik Ampera; Mumuh Muhsin Zakaria (Universitas Padjadjaran, 2022)
Folklore about Dewi Sri, the goddess of fertility in Indonesian culture has various versions. The version of the folklore used in this article is the Sundanese version “Nyi Mas Sanghyang Dewi Sri” collected in a research done by lecturers of Faculty of Cultural Sciences, Universitas Padjadjaran. The folklore is represented in a written text in Sundanese language as the source language text and from the text, it is represented in Indonesian language as the first target language text, then in English language as the second target language text. How the folklore is represented in three languages and what methods of translation are used in target language texts are the objectives of this research. The research method used is descriptive-comparative method. The results show that the folklore is represented in different ways; some additional information are added particularly in the English target text and the method of translation used in the two target languages is mostly communicative translation but in the second target language text, free translation is also found. Despite these differences, the message that needs to be conveyed about Nyi Mas Sanghyang Dewi Sri as the goddess of fertility remains the same in all texts.